2022
DOI: 10.1111/jace.18552
|View full text |Cite
|
Sign up to set email alerts
|

High hardness (TiZr)C ceramic with dislocation networks

Abstract: Raising the configurational entropy in a solid solution ceramic is regarded as a promising strategy to improve the mechanical properties of ceramics, especially when five or more elements are mixed to form so-called high-entropy ceramics. However, in this study, we report that the binary (TiZr)C solid solution ceramics can demonstrate high hardness comparable or even superior to high-entropy ceramics. Followed by a carbothermal reduction synthesis of carbide powders, the bulk ceramics were synthesized by hot p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…43 However, the mechanical performance of these two types of porous ferroelectric ceramics is often limited by the inhomogeneity of the structure. The 3-1 type materials (aligned pores in a continuous ceramic matrix) and 2-2 type materials (alternating 2-D layers of ceramic and pores) exhibit improved piezoelectric properties due to the orientation of piezoelectric phase in the poling direction, 42,44 for example, porous BCZT ceramic with 2-2 type structure possessed a higher remnant polarization compared to a 3-0 structure due to greater fraction of poled regions in ceramics. 45 Less research has been undertaken of 3-1 and 2-2 type porous structures, and it would be of interest to undertake more research in this area in an effort to improve level of polarization and facilitate the poling process.…”
Section: Porous Ferroelectric Ceramicsmentioning
confidence: 99%
See 1 more Smart Citation
“…43 However, the mechanical performance of these two types of porous ferroelectric ceramics is often limited by the inhomogeneity of the structure. The 3-1 type materials (aligned pores in a continuous ceramic matrix) and 2-2 type materials (alternating 2-D layers of ceramic and pores) exhibit improved piezoelectric properties due to the orientation of piezoelectric phase in the poling direction, 42,44 for example, porous BCZT ceramic with 2-2 type structure possessed a higher remnant polarization compared to a 3-0 structure due to greater fraction of poled regions in ceramics. 45 Less research has been undertaken of 3-1 and 2-2 type porous structures, and it would be of interest to undertake more research in this area in an effort to improve level of polarization and facilitate the poling process.…”
Section: Porous Ferroelectric Ceramicsmentioning
confidence: 99%
“…Moreover, different parts of the sample exhibited a different dielectric constant due to a change in the orientation level of pores at different locations. 44 Porous ferroelectric ceramics with various orientation angles of 0°, 45° and 90° with respect to the poling direction were fabricated by camphene-based freeze casting. The material with a 0° orientation exhibited a higher dielectric constant compared to the material with a 90°orientation, since the alignment of pores in the poling direction resulted in an increase in the volume fraction and degree of interconnection of the piezoelectric material in the direction of interest.…”
Section: Dielectric Propertiesmentioning
confidence: 99%
“…thermal conductivity and good oxidation resistance, has become the most promising candidate material in the aerospace field. [1][2][3][4][5][6][7] In many studies, medium-entropy ceramics have attracted much attention because of their huge application potential. Recent studies have found that increasing configurational entropy is an effective way to toughen ceramic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Medium‐entropy ceramics are generally composed of three or four metal elements; its configurational entropy is between high entropy ceramics (Sconf > 1.5R, R is the gas constant) and low entropy ceramics (Sconf < 1.0R), because of its high hardness, high melting point, high thermal conductivity and good oxidation resistance, has become the most promising candidate material in the aerospace field 1–7 . In many studies, medium‐entropy ceramics have attracted much attention because of their huge application potential.…”
Section: Introductionmentioning
confidence: 99%
“…Porosity has been suggested as an efficient structuring tool to enhance the electrical power output of the piezoelectric harvesters because the introduction of pores inside the material can substantially lower the effective relative permittivity. [ 6–13 ] For example, a porous thick film of PbZrTiO 3 (PZT) with 60% porosity has been demonstrated, and a reduction in relative permittivity by a factor of three has been reported. [ 14 ] For piezoelectric polymers, namely poly(vinylidenefluoride) (PVDF) and its random copolymers with trifluoroethylene, P(VDF‐TrFE), porous thick‐films and fibres have been realized using solution processing, melt‐casting, and porous anodized alumina templates.…”
Section: Introductionmentioning
confidence: 99%